2013
DOI: 10.1073/pnas.1310201110
|View full text |Cite
|
Sign up to set email alerts
|

H19 lncRNA controls gene expression of the Imprinted Gene Network by recruiting MBD1

Abstract: The H19 gene controls the expression of several genes within the Imprinted Gene Network (IGN), involved in growth control of the embryo. However, the underlying mechanisms of this control remain elusive. Here, we identified the methyl-CpG-binding domain protein 1 MBD1 as a physical and functional partner of the H19 long noncoding RNA (lncRNA). The H19 lncRNA-MBD1 complex is required for the control of five genes of the IGN. For three of these genes-Igf2 (insulin-like growth factor 2), Slc38a4 (solute carrier f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
202
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(214 citation statements)
references
References 38 publications
12
202
0
Order By: Relevance
“…According, recent advances sustain an interplay among ICR1 and other iDMRs (our unpublished data) and chromatin interactions between H19 and portions of chromosome 7 [34]. MEST methylation may also be part of an imprinting gene network (IGN), involving the trans -acting functions of H19 lncRNA [35,36]. Further investigations are requested to better elucidate this finding.…”
Section: Discussionmentioning
confidence: 92%
“…According, recent advances sustain an interplay among ICR1 and other iDMRs (our unpublished data) and chromatin interactions between H19 and portions of chromosome 7 [34]. MEST methylation may also be part of an imprinting gene network (IGN), involving the trans -acting functions of H19 lncRNA [35,36]. Further investigations are requested to better elucidate this finding.…”
Section: Discussionmentioning
confidence: 92%
“…Although heritable changes in gene regulation that occur via modification of the DNA without changes to the DNA sequence are often referred to as epigenetic programming, noncoding RNA (ncRNA)-mediated transcriptional or posttranscriptional regulation is one of the major regulation mechanisms for epigenetic programming (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Recent studies have identified thousands of long ncRNAs (lncRNAs) (17,23) in mammalian genomes that regulate gene expression in a variety of immunological processes (31)(32)(33)(34)(35), such as differentiation of T cells (33,36) and dendritic cells (DCs) (35).…”
Section: T Uberculosis (Tb) Caused By Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%
“…H19 is a sensitive imprinted gene, which contains a regulatory domain that is vulnerable to manipulation in vitro (Fauque et al, 2007). Moreover, H19 controls the gene expression of the imprinted gene network by recruiting MBD1, which is involved in individual growth and development (Monnier et al, 2013). The results of previous studies showed that a CpG-island in intron 2 of IGF2R carries a maternal-specific methylation imprint that could act as an imprinting signal to maintain the expression of the maternal allele.…”
Section: Discussionmentioning
confidence: 99%